Langerhans cell histiocytosis in an adult patient - A. E. Karamova; V. V. Chikin; L. F. Znamenskaya; M. A. Nefedova; V. A. Mikhina; N. S. Battalova (State Scientific Center of Dermatovenereology and Cosmetology, 2019)
Aim: to present a clinical case of a rare dermatosis - Langerhans cell histiocytosis (LCH) in an adult patient.Materials and methods. A clinical and laboratory examination of a 64-year-old woman who had complained of rashes on the skin of the scalp, neck, trunk and lower extremities accompanied by itching was carried out. A histological study of skin biopsy samples from the lesion area, as well as an immunohistochemical study of Langerhans cell markers - langerin and S-100 protein - were performed.Results. Clinical manifestations of the disease, the presence of histiocytic infiltrate in the epidermis and dermis during the histological study and immunohistochemical detection of langerin infiltrate cells and S-100 protein were all consistent with the diagnosis of LCH. The therapy with methotrexate subcutaneously significantly improved the patient's condition.Conclusion. Verification of the LCH diagnosis requires a histological study of skin biopsy samples and an immunohistochemical study of Langerhans cell markers. The efficacy of methotrexate in the treatment of this disease has been confirmed.